Aplikasi Katalis Homogen Pada Sintesis Emulsifier - Rizki Agustina; Ida Zahrina; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Monoglycerides and diglycerides are a form of emulsifier. Mono- and di-glycerides can be synthesized in various ways, one of which is esterification. In the esterification process, the use of a catalyst is very important in advance of the fatty acid conversion results. Homogeneous catalysts are mostly used in this process. Homogeneous catalysts are compounds that have the same phase as the reactants when a chemical reaction takes place. One of the newest forms of the catalyst with